Expand and Simplify (2x + 1)(x – 2)(x + 3)

Question

Expand and Simplify
(2x + 1)(x – 2)(x + 3)

in progress 0
Nevaeh 3 weeks 2021-09-24T05:16:38+00:00 1 Answer 0

Answers ( )

    0
    2021-09-24T05:17:41+00:00

    Answer:

    Answer is =2x^3+3x^2-11x-6

    Step-by-step explanation:

    First of all multiply first and second bracket.

    =x(2x+1) -2(2x+1)

    =2x^2+x-4x-2

    =2x^2-3x-2

    Now multiply 2x^2-3x-2 with (x+3)

    =x(2x^2-3x-2) +3(2x^2-3x-2)

    =2x^3-3x^2-2x+6x^2-9x-6

    =2x^3+3x^2-11x-6

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )